2024
DOI: 10.7150/ijbs.91543
|View full text |Cite
|
Sign up to set email alerts
|

mtDNA-cGAS-STING axis-dependent NLRP3 inflammasome activation contributes to postoperative cognitive dysfunction induced by sevoflurane in mice

Nan-Shi-Yu Yang,
Wen-Jing Zhong,
Han-Xi Sha
et al.

Abstract: The activation of NLRP3 inflammasome in microglia is critical for neuroinflammation during postoperative cognitive dysfunction (POCD) induced by sevoflurane. However, the molecular mechanism by which sevoflurane activates the NLRP3 inflammasome in microglia remains unclear. The cGAS-STING pathway is an evolutionarily conserved inflammatory defense mechanism. The role of the cGAS-STING pathway in sevoflurane-induced NLRP3 inflammasome-dependent neuroinflammation and the underlying mechanisms require further inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Feng et al showed that endoplasmic reticulum stress-mediated activation of ATF3 contributes to sevoflurane-induced neuronal iron overload via H 2 O 2 accumulation and resulting iron overload [ 30 ]. Another study showed that sevoflurane caused mitochondrial ROS production and elevated cytoplasmic calcium levels, triggering the opening of the mitochondrial permeability transition pore (MPTP) and lowering the mitochondrial membrane potential (MMP), inducing mitochondrial iron overload, and ultimately leading to cognitive dysfunction [ 31 ]. The peripheral auditory nervous system is similarly susceptible to damage by drugs and the environment [ 7 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Feng et al showed that endoplasmic reticulum stress-mediated activation of ATF3 contributes to sevoflurane-induced neuronal iron overload via H 2 O 2 accumulation and resulting iron overload [ 30 ]. Another study showed that sevoflurane caused mitochondrial ROS production and elevated cytoplasmic calcium levels, triggering the opening of the mitochondrial permeability transition pore (MPTP) and lowering the mitochondrial membrane potential (MMP), inducing mitochondrial iron overload, and ultimately leading to cognitive dysfunction [ 31 ]. The peripheral auditory nervous system is similarly susceptible to damage by drugs and the environment [ 7 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%